2015
DOI: 10.3892/mmr.2015.4747
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of black tea extract against oxidative DNA damage in human lymphocytes

Abstract: The aim of the present study was to examine the genoprotective and radioprotective effects of black tea extract (BTE) against the induction of single strand DNA breaks in human lymphocytes subjected to hydrogen peroxide (H2O2) or gamma-rays (2 Gy dose). Lymphocytes were incubated with or without different concentrations of BTE (0.005-500 µg/ml) for 30 min, followed by treatment with or without H2O2 (0.088 µmol/l) for 5 min. To examine the radioprotective effect of BTE, the lymphocytes were incubated with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
2
4
0
1
Order By: Relevance
“…G. dinarica extract elevated the frequency of micronuclei and enhanced apoptosis in peripheral blood lymphocytes ( 34 ). Similar results were found for many plant extracts known for their antioxidant activity and rich in polyphenols, such as black and green tea extract, suggesting that higher polyphenol concentrations could lead to spontaneous H 2 O 2 generation, DNA damage, and cell death ( 35 , 36 ). In line with this argument, the concentration determines whether certain compound or extract acts as anti- or pro-oxidant.…”
Section: Discussionsupporting
confidence: 78%
“…G. dinarica extract elevated the frequency of micronuclei and enhanced apoptosis in peripheral blood lymphocytes ( 34 ). Similar results were found for many plant extracts known for their antioxidant activity and rich in polyphenols, such as black and green tea extract, suggesting that higher polyphenol concentrations could lead to spontaneous H 2 O 2 generation, DNA damage, and cell death ( 35 , 36 ). In line with this argument, the concentration determines whether certain compound or extract acts as anti- or pro-oxidant.…”
Section: Discussionsupporting
confidence: 78%
“…These findings confirm the hypothesis that lentil sprout extract offers a protective effect against radiation by inhibition of ROS production. Although some plant such as Zataria multiflora ( 17 ) and black tea( 29 ) show more radioprotective effect, comparison to our result with studied cereal like wheat( 30 ) and legume like peanut( 31 ), lentil sprout demonstrated appropriate radioprotective efficiency. This study gives new insights into the role of lentil sprout extract in attenuating lymphocyte damage induced by radiation.…”
Section: Discussionsupporting
confidence: 47%
“…Our results confirmed that DTE could decrease the ROS levels elevated by IR. In addition, DNA injury induced by IR was determined by H2AX phosphorylation, and this was used as an index for quantifying DNA double-strand breaks [ 33 36 ]. The data suggested that DTE could mitigate DNA injury induced by IR.…”
Section: Discussionmentioning
confidence: 99%